2000
DOI: 10.1097/00001648-200003000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Inflammation of the Ovarian Epithelium and Risk of Ovarian Cancer

Abstract: Previous epidemiologic observations consistently suggest that suppression of ovulation, tubal ligation, and hysterectomy reduce the risk of ovarian cancer and that perineal talc use increases the risk. We examined these and other risk factors in the context of a new hypothesis: that inflammation may play a role in ovarian cancer risk. Ovulation entails ovarian epithelial inflammation; talc, endometriosis, cysts, and hyperthyroidism may be associated with inflammatory responses of the ovarian epithelium; gyneco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
228
1
11

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(247 citation statements)
references
References 36 publications
7
228
1
11
Order By: Relevance
“…After adjusting for age, number of pregnancies, family history of ovarian cancer, race, oral contraceptive use, tubal ligation, hysterectomy and breastfeeding; women with ovarian cancer were 1.7-fold more likely to have reported a history of endometriosis than controls. 15 These data are consistent with an earlier report of a 2.5-fold increased risk of ovarian cancer in endometriosis patients, with the risk increasing to 4.2-fold in those with a history of ovarian endometriosis. 16 However, despite the histological and epidemiological evidence linking these two diseases, it is still unclear whether endometriosis is a precursor to EAOCs, or whether there is an indirect link involving common environmental, immunological, hormonal or genetic factors.…”
supporting
confidence: 92%
“…After adjusting for age, number of pregnancies, family history of ovarian cancer, race, oral contraceptive use, tubal ligation, hysterectomy and breastfeeding; women with ovarian cancer were 1.7-fold more likely to have reported a history of endometriosis than controls. 15 These data are consistent with an earlier report of a 2.5-fold increased risk of ovarian cancer in endometriosis patients, with the risk increasing to 4.2-fold in those with a history of ovarian endometriosis. 16 However, despite the histological and epidemiological evidence linking these two diseases, it is still unclear whether endometriosis is a precursor to EAOCs, or whether there is an indirect link involving common environmental, immunological, hormonal or genetic factors.…”
supporting
confidence: 92%
“…CXC chemokines in epithelial ovarian cancer Ness et al 2000, Fleming et al 2006, Son et al 2007, Coffelt & Scandurro 2008, Maccio & Madeddu 2012. As key mediators of inflammation, chemokines play two major roles: i) they are responsible for the recruitment and activation of immune cells into sites of malignancy (and possibly areas of pre-neoplastic growth) and ii) they mediate pro-and anti-angiogenic effects, processes required for the vascularisation and progression of tumours.…”
Section: Inflammation and The Ovarian Surface Epitheliummentioning
confidence: 99%
“…Factors related to inflammation of the OSE have been associated with increased risk of ovarian cancer (Ness and Cottreau, 1999;Ness et al, 2000) and exposure to anti-inflammatory agents has been shown to inhibit tumour invasion and protease production by ovarian carcinoma cells (Akhmedkhanov et al, 2001). It is therefore of obvious interest that all cell lines studied here appear to have largely lost their capacity to mount an inflammatory response to IL-1a in terms of increased 11bHSD-1 expression and hence increased formation of anti-inflammatory, proapoptotic glucocorticoids.…”
Section: Discussionmentioning
confidence: 96%
“…Repeated episodes of ovulation-associated injury and repair are presumed to underlie the high frequency of ovarian carcinoma arising from the OSE (Fathalla, 1971;Salazar et al, 1996), which account for 90% of all ovarian cancers (Ozols, 1991). Since ovulation is a natural inflammatory process (Espey, 1980a, b), factors related to inflammation of the OSE have been associated with increased risk of ovarian cancer (Ness and Cottreau, 1999;Ness et al, 2000). It is therefore critically important to understand how inflammatory cell damage is normally resolved in the OSE.…”
mentioning
confidence: 99%